Features of diagnostics and surgical treatment of right ventricular thrombosis complicated by pulmonary artery thromboembolism (clinical case) - Vitovsky, R. M.; Semeniv, P. M.; Rusnak, A. O.; Ivanov, Y. R.; Onischenko, V. F. (Ukrainian Journal of Cardiovascular Surgery, 2019)
The case of differential diagnosis and treatment of a patient with pulmonary embolism (PE), the source of which was the thrombus formed in the right ventricle of the heart, is presented. The peculiarity of this case was the untimely diagnosis of the disease, which simulated pneumonia, the treatment of which did not improve the clinical condition of the patient. Tomography allowed to determine the thrombosis of the right branch of the pulmonary artery and to send the patient to the cardiac surgery center for further treatment. Diagnosis of a probable source of embolism occurred after echocardiography, which revealed a tumor-like lesion of the right ventricle of large size and dense consistency. The results of surgical treatment of the patient, during which extensive formation of the right ventricle was removed, a dense elastic consistency with signs of fragmentation confirmed the prediction of this particular source of pulmonary embolism. Removal of blood clots from the right branch of the pulmonary embolism showed their similar macrostructure with right ventricular formation. The appearance and macrostructure of the formation did not allow to determine with certainty its character. Only histological examination was able to determine the thrombogenicity of the origin of this formation. The recurrent nature of pneumonia, without the presence of risk factors, in young patients may be the basis for more thorough examination to identify atypical clinical conditions. The restoration of the source of the body is of great importancefor the prevention of its relapse. Finding the source of pulmonary embolism should necessarily include echocardiography to carefully examine possible lesions of intracardiac structures with the formation of blood clots that may be responsible for its occurrence.